Russian people in the D.S. Lvov`s concept of national economic growth - S. A. Antonov (Вестник университета)
The conditions for ensuring national economic growth, as reflected in the works of D. S. Lvov has been considered. Three groups of relevant conditions, namely: basic (determining the existence of a people and allowing generally to speak about economic activity), dynamic (determining the intensity of economic growth), and targeted (concerning the formation of the future economic order) have been described. The main scientific and ideological position of D. S. Lvov has been disclosed − the Russian people are a strategic factor of national economic growth.